2015
DOI: 10.1080/10926771.2015.1009601
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Evaluation of Peer versus Professional Educators of a Bystander Program for the Prevention of Sexual and Dating Violence among College Students

Abstract: Some argue that bystander intervention programs for sexual violence (SV) and dating violence (DV) prevention should be facilitated by peer educators. However, there is no evidence that peer educators are more effective than professionals at delivering program material. This study experimentally evaluated a bystander prevention program; half of participants were assigned to peer educators and half to professionals. Multilevel modeling showed that peer educators had a significantly better effect at reducing some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The program was effective for the variables of general physical violence and physical violence against women, as the participants of the experimental group reduced their mean approval in these variables. When comparing these findings to those obtained in other programs for the prevention of partner violence in youth and adolescents, several programs were identified that have also reduced the mean in relation to attitudes and beliefs that justify partner violence in their experimental groups (i.e., Muñoz-Rivas, 2010; Póo and Vizcarra, 2011;Fernández, 2013;Hines and Palm Reed, 2015;McLeod et al, 2015;Velasco, 2015). It is important to note, however, that in the analysis of the scales used, most of these programs made no distinction between attitudes regarding physical and verbal violence or the gender of the victim.…”
Section: Discussion Attitudes Toward Violence In Intimate Partner Relmentioning
confidence: 87%
See 1 more Smart Citation
“…The program was effective for the variables of general physical violence and physical violence against women, as the participants of the experimental group reduced their mean approval in these variables. When comparing these findings to those obtained in other programs for the prevention of partner violence in youth and adolescents, several programs were identified that have also reduced the mean in relation to attitudes and beliefs that justify partner violence in their experimental groups (i.e., Muñoz-Rivas, 2010; Póo and Vizcarra, 2011;Fernández, 2013;Hines and Palm Reed, 2015;McLeod et al, 2015;Velasco, 2015). It is important to note, however, that in the analysis of the scales used, most of these programs made no distinction between attitudes regarding physical and verbal violence or the gender of the victim.…”
Section: Discussion Attitudes Toward Violence In Intimate Partner Relmentioning
confidence: 87%
“…Interestingly, addressing attitudes toward violence, gender roles and stereotypes, and socio-emotional competencies has been central to previous programs for the prevention of intimate partner violence in adolescence and youth. Programs addressing (1) attitudes toward partner violence can be seen in Jaffe et al (1992), Lavoie et al (1995), Avery-Leaf et al (1997), Weisz and Black (2001), Schwartz et al (2006), Alexander et al (2014), Miller et al (2014), Hines andPalm Reed (2015), McLeod et al (2015), and Velasco (2015), as well as other programs developed by Díaz-Aguado and Martínez-Arias (2001), Hernando-Gómez (2007), Muñoz-Rivas (2010), Póo and Vizcarra (2011), and Fernández (2013); (2) gender stereotypes, sexist beliefs and attitudes and negative gender attitudes in adolescence and young adulthood in Foshee et al (1998), Foshee et al (2000), Foshee et al (2004), Rainey and Rust (1999), Díaz-Aguado and Martínez-Arias (2001), Schwartz et al (2006), Miller et al (2014, and Velasco (2015); and (3) socioemotional competences such as self-esteem in Josephson and Proulx (1999) and Mateos-Inchaurrondo (2013), empathy in Hines and Palm Reed (2015), emotional intelligence in Murta et al (2013), and emotional skills in Wolfe et al (2009). Although all these programs have been implemented from adolescence onwards, the promotion of negative attitudes toward violence and gender inequality, and socioemotional learning are all aspects of paramount importance for children in primary education (Durlak, 1997;Durlak et al, 2010Durlak et al, , 2011Rimm-Kaufman and Hulleman, 2015).…”
Section: The Development Of a Program For The Prevention Of Partner Vmentioning
confidence: 99%
“…In one peer education course among college fraternity members, students reported understanding sexual violence material in a contextual manner that helped them to have more emotional connections to what they were learning [8]. Other studies have found that peer-led programs focused on sexual violence are most effective at reducing rape myth acceptance [9], decreasing violence among men [10], and may have effects on bystander attitudes and efficacy [11] (although a meta-analysis by Jouriles et al, 2018 did not support this [12]). At the University of Michigan (UM), a peer-led primary prevention program for first-year students, aimed at reducing sexual violence, began in 2011.…”
Section: Peer-led Prevention Programsmentioning
confidence: 99%
“…Many studies that did not report specific MOPs summarized the steps that the research team had taken to improve program performance, such as feedback or refresher courses for instructors (e.g., "All facilitators received a 1-day training on how to deliver the program, were then able to practice their skills on a group of orientation leaders prior to delivering the program, and received feedback on their presentation skills and adherence to the program from the codirectors of the program. Facilitators who had received training in previous years received a 3-hour refresher course on how to deliver the program" [Hines and Reed, 2015]). Thus, more than 20-25 percent of the studies were addressing program performance issues, even if they did not assess them with a standardized MOP in the published article.…”
Section: Measures Of Performancementioning
confidence: 99%